Dutch word stress as pronounced by Indonesian students - Roosman, Lilie M. (UI Scholars Hub, 2009)
This study focuses on the way in which the Dutch monophthongal vowels are pronounced by Indonesian students. To investigate whether Indonesian students realize the Dutch vowels correctly, especially when they are stressed, I analysed duration and quality of stressed and unstressed Dutch vowels. Measurements were done on the duration and the formant frequencies of the vowels spoken by Indonesian students and by native speakers of Dutch as well. Statistical analysis showed that in general the differences in duration between vowels spoken by the Indonesian students and by the native speakers were not significant. However, the effect of stress on the lengthening of the vowels was stronger for the Indonesian students than for the native speakers. In addition, statistical analysis of the formant frequencies confirmed that the non-native speakers realized the Dutch vowels slightly differently from the Dutch native speakers. The Indonesian students pronounced the stressed vowels more clearly than their unstressed counterparts; yet their vowel diagram is smaller than the vowel diagram of the native speakers.